Probiotic Drugs Impact on the Innate Immunity Factors - Oksana Nikolaeva (Journal of Global Pharma Technology, 2016)
Probiotics are the drugs containing living microorganisms related to normal physiological intestinal flora. Recently probiotic drugs are made based on microorganisms’ pp. Bifidobacterium, Lactobacterium, apathogenic strains pp. Streptococcus, Enterococcus, acquired from the humans and animals’ gastrointestinal tract. These microorganisms have a certain impact on the innate immunity factors, interacting with the lymphoid intestinal system. The studies were aimed at examination of the probiotic drugs impact on the innate immunity factors. 60 newborn calves of black-motley breed and 60 piglets of large white breed of 45-day weaning became the object of the study. Blood draw of newborn calves and weaned piglets for immunological studies was performed before the study and then on the 10th, 20th and 30th day of the study. When examining the innate immunity factors there were defined such factors as lysozyme activity in blood serum, blood serum bactericidal factors value and phagocytosis system factors. It was stated that the animals treated with the probiotic drugs based on L. plаntаrum 8P-А3 and synbiotic drugs based on L. plаntаrum 8P-А3 as well as on the medicinal plant materials have the innate immune factors activated with age.Key words: L. plаntаrum 8P-А3, innate immunity, Chеlidоnium mаjus L., Bеrbеris vulgаris, blood phagocytic activity.